Distributed denial of government: the Estonian Data Embassy Initiative. Issue 9 (September 2017) - Robinson, Nick; Martin, Keith
Abstract : In an age of increasing and evolving cyber-attacks and disruption, recent events have shown that threats to critical national infrastructure and vital government services are both genuine and effective. In light of this, what measures might a government be willing to take in order to safeguard its critical infrastructure and ever-expanding 'digital ecosystem'?